Differential Subordinations of Arithmetic and Geometric Means of Some Functionals Related to a Sector - A. Lecko; M. Lecko (International Journal of Mathematics and Mathematical Sciences)
Some general theorems on differential subordinations of some functionals connected with arithmetic and geometric means related to a sector are proved. These results unify a number of well known results concerning inclusion relation between the classes of analytic functions built with using arithmetic and geometric means.